THE EVALUATION OF A VIDEO-BASED TEXTBOOK FOR LISTENING FOR GENERAL PURPOSES SUBJECT - Hustarna Hustarna (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
Textbooks are essential in education. They are used as learning tools to facilitate the teaching and learning process. Before deciding what textbooks will be used or whether the textbook is still appropriate, it is essential to evaluate it. This present study aims at evaluating a video-based textbook for Listening for General Purposes. The research used a content or document analysis approach, which belongs to a descriptive qualitative study (Ary et al., 2010). The instrument was a rubric containing criteria for good textbooks. The data were analyzed qualitatively based on the criteria of designing good textbooks. The finding shows that the textbook is good in terms of language and practicality. The textbook is very practical for lecturers who teach the listening subject in that it gives very clear steps for the lecturers on how to teach each unit of the book. On the other hand, the textbook and videos used still have some weaknesses. They relate to the appropriateness of the contents of the textbook and videos used with the curriculum and students' language level and the quality of the layout. The layout is just like a module. In addition, the quality of some audio and visuals is still bad. Many videos still have subtitles that do not match with the objective of using the videos, namely, to improve students' listening ability.